New directions in elite studies - Korsnes, Olav; Hjellbrekke, Johs. 1965-; Bühlmann, Felix 1975-; Savage, Michael 1959- (Routledge, Taylor & Francis Group, 2019)
Since the financial crisis, the issue of the 'one percent' has become the centre of intense public debate, unavoidable even for members of the elite themselves. Moreover, inquiring into elites has taken centre-stage once again in both journalistic investigations and academic research. New Directions in Elite Studies attempts to move the social scientific study of elites beyond economic analysis, which has greatly improved our knowledge of inequality, but is restricted to income and wealth. In contrast, this book mobilizes a broad scope of research methods to uncover the social composition of the power elite - the 'field of power'. It reconstructs processes through which people gain access to positions in this particular social space, examines the various forms of capital they mobilize in the process - economic, but also cultural and social capital - and probes changes over time and variations across national contexts.Bringing together the most advanced research into elites by a European and multidisciplinary group of scholars, this book presents an agenda for the future study of elites. It will appeal to all those interested in the study of elites, inequality, class, power, and gender inequality
Literaturangaben
Keywords: Elite (Social sciences); Social classes; Power (Social sciences); Elite; Konferenzschrift -- 2015 -- London